2005
DOI: 10.1614/ws-03-141r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Rice and red rice interference. I. Response of red rice (Oryza sativa) to sowing rates of tropicaljaponicaandindicarice cultivars

Abstract: Field experiments were conducted at the Rice Research and Extension Center at Stuttgart, AR, in 1997 and 1998 to evaluate the growth response of Stuttgart strawhull (Stgstraw) red rice to sowing densities of 0, 50, 100, and 150 kg ha−1of ‘Kaybonnet,’ ‘Guichao,’ and ‘PI 312777’ rice cultivars. PI 312777 produced a greater leaf area index and tiller density than Kaybonnet when grown with red rice. In 1997, Stgstraw seed yields were lower when grown with PI 312777 and Guichao than with Kaybonnet. The increased we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 29 publications
0
27
2
1
Order By: Relevance
“…In addition, different rice cultivars can also respond differently to weedy rice variants. In a study in the United States, rice 'Kaybonnet' was found to be less competitive than 'PI 312777' against weedy rice biotypes (Estorninos et al, 2005). Ratnasekera et al (2013) evaluated the interactions of weedy rice with improved rice (At 362) under transplanting and direct seeding conditions where the general performance of weedy rice was higher with or without competition.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, different rice cultivars can also respond differently to weedy rice variants. In a study in the United States, rice 'Kaybonnet' was found to be less competitive than 'PI 312777' against weedy rice biotypes (Estorninos et al, 2005). Ratnasekera et al (2013) evaluated the interactions of weedy rice with improved rice (At 362) under transplanting and direct seeding conditions where the general performance of weedy rice was higher with or without competition.…”
Section: Weedy Rice Biology and Competition With Cultivated Ricementioning
confidence: 99%
“…This study suggested that increasing rice crop interference could significantly reduce weedy rice growth. Estorninos et al (2005) stated that the above-ground biomass and weedy rice grain yield decreased with the increase in the cultivated rice seeding rate from 50 to 150 kg ha -1 and, at the same time, rice yield increased with increased crop seeding rates in weedy rice infested fields. High seeding rates could improve the successful reduction of herbicide rates and perceived risks connected to the environmental effect of this chemical.…”
Section: Seeding Rate and Row Seedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Weedy rice seedlings are often morphologically nearly identical to cultivated rice plants before they reach the reproductive stage, hindering detection and selective weeding. With a rapid growth rate, highly shattering seed, persistent seed dormancy, and dark, undesirable grains that contaminate harvests, weedy rice is considered one of the primary constraints on rice production and marketability in both temperate and tropical regions (Estorninos et al 2005; Gealy et al 2012; Merotto et al 2016). In addition, the potential for crop–weed gene flow threatens the long-term sustainability of weed control strategies that rely on herbicide-resistant rice cultivars (Pusadee et al 2013; Burgos et al 2014; Merotto et al 2016).…”
mentioning
confidence: 99%
“…O arroz-vermelho (Oryza sativa) é a principal planta daninha das áreas produtoras de arroz do mundo (Estorninos Jr. et al, 2005). Estimativas demonstram que o Rio Grande do Sul deixa de produzir o correspondente a 20% de sua produção de arroz devido à competição do arroz-vermelho (Gomes & Magalhães Jr., 2004).…”
Section: Introductionunclassified